Caste and the city: Urban aspirations and sensibility in hindi dalit short fiction - Zafir, Deeba (London Routledge, 2024)
This book looks at Dalits in the city and examines the nature of Dalit aspirations as well as the making of an urban sensibility through an analysis of hitherto unexamined short stories of some of the first- and second-generation as well as contemporary Dalit writers in Hindi.
Keywords: Asian Studies; South Asian Culture & Society; South Asian Philosophy